An Organocatalytic Newer Synthetic Approach toward the Access of Dihydropyrido[2, 3-d] Pyrimidine in Water: A Perfect Synergy for Eco-compatible Organic Synthesis. (26th November 2022) - Jadhav, Chetan K.; Nipate, Amol S.; Chate, Asha V.; Gill, Charansingh H.
Abstract: The simple and effective one-pot, three-component protocol for the synthesis of dihydropyrido[2, 3- d ]pyrimidine derivatives is presented using a 2-aminoethanesulfonic acid in water. Uracil annulated heterocycles were obtained using various aromatic/aliphatic aldehydes, 6-amino-1, 3-dimethyl uracil, and acetyl acetone at 60–80 °C in 2-aminoethanesulfonic acid and water as a green reaction medium. The product obtained was in good to excellent yield (90-94%) in minimum reaction time. Operational simplicity, easy workup, Superior green credentials and the catalyst could be recovered and reused for four consecutive cycles without appreciable loss in catalytic activity. Graphical Abstract: UF0001